2008
DOI: 10.1073/pnas.0805429106
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial proton transfer coupled to reduction of O 2 and NO by a heme-copper oxidase

Abstract: The heme-copper oxidase (HCuO) superfamily consists of integral membrane proteins that catalyze the reduction of either oxygen or nitric oxide. The HCuOs that reduce O 2 to H2O couple this reaction to the generation of a transmembrane proton gradient by using electrons and protons from opposite sides of the membrane and by pumping protons from inside the cell or organelle to the outside. The bacterial NO-reductases (NOR) reduce NO to N2O (2NO ؉ 2e ؊ ؉ 2H ؉ 3 N2O ؉ H2O), a reaction as exergonic as that with O2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 34 publications
2
46
1
Order By: Relevance
“…We previously described the reaction between fully reduced wild-type R. sphaeroides cbb 3 reconstituted into vesicles and O 2 (10), where the reaction is characterized by a major oxidation phase (of all heme groups) with a time constant ðτÞ ¼ 1 ms. In this work the solubilized cbb 3 was studied, and the O 2 concentration was 1 mM instead of 0.6 mM in the previous study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously described the reaction between fully reduced wild-type R. sphaeroides cbb 3 reconstituted into vesicles and O 2 (10), where the reaction is characterized by a major oxidation phase (of all heme groups) with a time constant ðτÞ ¼ 1 ms. In this work the solubilized cbb 3 was studied, and the O 2 concentration was 1 mM instead of 0.6 mM in the previous study.…”
Section: Resultsmentioning
confidence: 99%
“…Among the O 2 -reducing HCuOs, the cbb 3 type is the closest relative to NOR, and interestingly, cbb 3 -type oxidases, in contrast to A-type, have substantial NO-reduction activities (9,10). The A-type oxidases contain, in their catalytic subunit I, a lowspin heme a and a high-spin heme a 3 -Cu B active site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen binding network in our protein models may contribute to the fine-tuning of the Glu pK a to be more neutral, similar to that in NOR. Moreover, it is interesting that Cu(I)-I107E Fe B Mb also shows NOR activity, which provides an interesting protein model of HCOs with NOR function (26)(27)(28), even though Glu residues are not conserved in native HCOs. Additionally, spectroelectrochemical studies showed that the reduction potential of I107E Fe B Mb with no metal ion in the Fe B site is similar to that of Fe B Mb, but much lower than that of Cu B Mb (77 mV) (54), which contains the same three His, but no Glu in the metal-binding site above the heme.…”
Section: Discussion Using Rationally Designed Proteins To Address Impmentioning
confidence: 99%
“…In addition, two conserved glutamates, shown by modeling to be close to the Fe B site (21,22), are found to be essential for NOR activity (24,25). Some members of HCOs such as cytochrome cbb 3 oxidase display NOR activity (26)(27)(28), although the activity is ∼50-fold lower than native NOR (26). Therefore, it is important to elucidate the structural features, specifically the roles of the conserved glutamates close to the Fe B site and metal ions (copper vs. iron), responsible for the reduction of NO to N 2 O.…”
mentioning
confidence: 99%